Prospective comparison between a peristaltic pump and vacuum containers for paracentesis: Time, resources and safety - Lewis, Paul Bennett (Clinical imaging, 2024)
To meet the increasing demand for radiology departments to perform paracenteses, this study was done to compare the operational, financial and clinical impact of draining ascites with a peristaltic pump versus conventional vacuum containers. Prospective cohort study of 157 paracenteses (56 subjects) drained with ACCEL® evacuated drainage bottles (B. Braun Interventional Systems, Bethlehem, PA) and 159 paracenteses (53 subjects) drained with the RenovaRP® pump (Laborie Medical Technologies Corp., Portsmouth, NH). A short elective questionnaire was then distributed to the procedure staff and the subjects drained by both methods. Mean volume drained with the pump (5 L) was comparable to that drained by vacuum containers (4.9 L, p = 0.77). Mean time to drain subjects with the pump (18.6 min) was 9.1 min shorter and 3.8 min less variable than subjects drained with vacuum containers (27.7 min). This difference was statistically significant (p < 0.01) and clinically important (effect size = 0.73). Flow rate with the pump (4 min/L) was significantly faster (p < 0.05) than vacuum containers flow rate (6.6 min/L). No adverse events occurred in either group. Use of the pump increased the average cost by 21% and reduced earnings by 3%. All assistants (n = 6) and patients (n = 10) that responded to the questionnaire recommended the use of the pump over vacuum containers. The peristaltic pump safely drains ascites significantly faster and with less variability in time than vacuum containers. While use of the pump slightly increases cost per paracentesis, it was recommended by all paired subjects undergoing a paracentesis and all personnel assisting in the procedure. [Display omitted] •The RenovaRP® peristaltic pump drains ascites significantly faster and more consistently than conventional vacuum containers.•The reduction in time needed to drain ascites by using the peristaltic pump was a clinically important change.•Draining ascites with a peristaltic pump was just as safe as draining with conventional vacuum bottles.•The increased cost by using a peristaltic pump may be offset by patient and personnel satisfaction.